Thrombocytopenia and Non-Expression of Tn And TF Antigens Define Non-Metastasizing Breast Cancer in Serial Transplants of Dimethyl Benz(A)Anthracene Induced Mammary Tumours in Sprague Dawley Rats (Sahel Journal of Life Sciences FUDMA, 2023)
Functional mammary tumours were generated as serial transplants of dimethyl benz(a)anthracene (DMBA) in immunosuppressed Sprague Dawley rats (SD). These serial transplants were evaluated for their cellular behaviour and biomarkers. Breast cancer was induced by 10 mg/kg of 7, 12 dimethylbenzanthracene (DMBA) in 10 female SD rats. Following tumour development, the primary tumour was passaged into apparently healthy rats for first and second serial transplants. Cellular behaviour and biomarkers of transplants included growth of tumour, haematological indices, expression pattern of Tn and TF antigens and TNF-alpha. An elevation of TNF-Î±, non-induction of Tn antigen with thrombocytopenia were observed in the serial transplants derived from a malignant tumour induced by 7, 12, DMBA in female Sprague Dawley rats. Furthermore, neutrophil to lymphocyte and platelet to lymphocyte ratios were found to be significantly low in animals from the first serial transplant while being significantly high in animals of the second serial transplant group. Results indicate that DMBA-induced mammary tumours in Sprague Dawley rats undergo divergent cellular behaviour and antigenic expressions during serial transplantation.